"Musique cannibale": The Evolving Sound of Indigeneity in Heitor Villa-Lobos's Tres poêmas indigenas. (12th January 2021) - Burns, Chelsea
Abstract: Heitor Villa-Lobos's Tres poêmas indigenas (1926, published 1929) provide an unusual image of Brazilian indigeneity: in three short songs, he creates a narrative of progress, one that ends with redefining himself and modernist colleague Mário de Andrade as Amerindian. The first two songs set melodies collected in 1557 and 1912, the third a new poem by Andrade (1926). The set begins with a narrow pitch collection, thin textures, and ostinatos and ends with a lied-like approach to text–music relations. In this way, Villa-Lobos creates an evolving image of Amerindian music-making that capitalizes on Indianist fantasies while redefining indigeneity as encompassing even the most modern and urbane Brazilians.